2006
DOI: 10.1002/jrs.1518
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared spectra of carbonates of calcite structure

Abstract: The Raman and mid-range infrared spectra have been measured on natural limestone and dolomite minerals. The carbonate minerals show four prominent absorption bands in the regions 1450-1420, 890-870, 720-700 and 1000-1100 cm −1 . The positions of the wavenumbers are unique for each carbonate mineral and are thus diagnostic of their mineralogy. Calcite and dolomite groups are characterized by the Raman wavenumbers at 288 and 309 cm −1 and the infrared absorption bands at 712 and 728 cm −1 , respectively. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
287
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(336 citation statements)
references
References 20 publications
39
287
0
10
Order By: Relevance
“…Long et al [34] reported that peaks at 724, 726, and 730 cm −1 were obtained from calcite particles including 30 mol% Mg. Similarly, Gunasekaran et al [34,35] and Xu and Poduska [36] reported dolomite peaks at 729 and 730 cm −1 , respectively. These peaks arose from CO 3 2− .…”
Section: Characterization Of Suspended Particles From Co 2 Mineralizamentioning
confidence: 76%
See 2 more Smart Citations
“…Long et al [34] reported that peaks at 724, 726, and 730 cm −1 were obtained from calcite particles including 30 mol% Mg. Similarly, Gunasekaran et al [34,35] and Xu and Poduska [36] reported dolomite peaks at 729 and 730 cm −1 , respectively. These peaks arose from CO 3 2− .…”
Section: Characterization Of Suspended Particles From Co 2 Mineralizamentioning
confidence: 76%
“…CO3 2− ions in dolomite also absorbed IR near this position, at 853 cm −1 . Meanwhile, the peak at 877 cm −1 indicates the presence of CaCO3 [35,36,[38][39][40]. Although we expected that the third and fourth cycles would produce Mg carbonates that excluded Ca, some of the Ca remaining in the suspension after the second cycle managed to participate in the carbonation of Mg.…”
Section: Characterization Of Suspended Particles From Co 2 Mineralizamentioning
confidence: 99%
See 1 more Smart Citation
“…Первая (1395.5 cm −1 ) соответствует поперечным, а вторая (1550 cm −1 ) -продольным коле-баниям кристаллической решетки кальцита [21][22][23][24].…”
Section: данные рамановской спектроскопииunclassified
“…The spectrum of the sample core after acid exposure resembled the unexposed sample. The surface of the CPC was primarily composed of sulfates; the presence of weak bands at 1220 cm (Gunasekaran et al, 2006;Xyla and Koutsoukos, 1989;Ylmen and Jaglid, 2013), the calciumsilicate-hydrate-related Si-O asymmetric stretching (V as Si-O ) in the silicate (SiO 4 −4 ) wide band at 965 cm −1 (Mollah et al, 2000;Taddei et al, 2014) and the three quartz-related bands at 1080, 799 and 693 cm −1 (Guan et al, 2014;Ramasamy and Suresh, 2009;Saikia et al, 2008). The spectrum from the core of the acid-exposed sample was similar to that of the control.…”
Section: Analyses Of Degraded Samples -Atr-ftir Measurementsmentioning
confidence: 99%